Technical guidelines for eDNA monitoring in Alpine waters - Eleršek, Tina (knjige, 2021)
Protocols for all eDNA monitoring steps! The present protocols are state-of-the-art today, but due to continuous revisions and technical improvements, they will be optimized in the near future.
Keywords: alpske dežele; Analize; biomonitoring; Celinske vode; Ekološko stanje; elektronske knjige; Okoljska DNA; Srednja Evropa; vode; Vrednotenje